Accurate prediction of the optical rotation and NMR properties for highly flexible chiral natural products12. Issue 35 (19th August 2016) - Hashmi, Muhammad Ali; Andreassend, Sarah K.; Keyzers, Robert A.; Lein, Matthias
Abstract : Despite advances in electronic structure theory the theoretical prediction of spectroscopic properties remains a computational challenge. Abstract : Despite advances in electronic structure theory the theoretical prediction of spectroscopic properties remains a computational challenge. This is especially true for natural products that exhibit very large conformational freedom and hence need to be sampled over many different accessible conformations. We report a strategy, which is able to predict NMR chemical shifts and more elusive properties like the optical rotation with great precision, through step-wise incremental increases of the conformational degrees of freedom. The application of this method is demonstrated for 3- epi -xestoaminol C, a chiral natural compound with a long, linear alkyl chain of 14 carbon atoms. Experimental NMR and [ α ]D values are reported to validate the results of the density functional theory calculations.